The relationship between emotional dependency on facebook and psychological well-being of adolescents aged 13-16 - Naeemi, Somayyeh; Tamam, Ezhar (Springer, 2017)
In most countries, Facebook is one of the top social networking sites among children and adolescents. Several studies have investigated the effect of Facebook dependency on individuals’ psychological well-being. However, inadequate studies have examined the impacts of Facebook in eudaimonic well-being. The current study explores how emotional dependence on Facebook relates to psychological well-being in eudaimonic approach. A total of 401, 13 to 16 yearsold who studied at an upper secondary school in Malaysia participated in this study. We expected a negative association between emotional dependence on Facebook and psychological wellbeing. The moderation effect of self-efficacy was examined in the current research. The results of structural equation modeling revealed that emotional dependence on Facebook negatively effects adolescents’ overall psychological well-being. The influence was more pronounced on autonomy, purpose in life, and positive relationship with others. The results also demonstrated that high self-efficacy did not reduce negative impacts of Facebook emotional dependence on adolescents’ psychological well-being.